Synthesis and Characterization of Metronidazole and Heterocycle Ester Dyads for Tyrosinase Inhibitory Activity (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Tyrosinase is an important copper-based enzyme mainly involved in skin pigmentation. The inhibition of the tyrosinase enzyme attracts importance in cosmetic and medicinal chemistry industry for its applications in skin whitening and anti-browning agents for humans as well as in food, agriculture industries. Imidazole based Metronidazole and its derivatives are widely accepted drug for wide range of diseases. Therefore, the present report involves the synthesis of heterocyclic derivatives of metronidazole and investigation of its efficacy towards the tyrosinase inhibitory activity. A series of metronidazole esters were synthesized and their chemical structures were confirmed using spectral techniques like, infrared spectroscopy (IR), proton nuclear magnetic resonance (1H-NMR), and liquid chromatography-mass spectrometry (LC-MS). All the compounds were evaluated for its tyrosinase inhibitory activity by oxidation of 3,4-dihydroxyphenylalanine in the presence of the synthesized esters(I-VIII) with kojic acid as standard. Among the synthesized compounds, VII (isonicotinic ester) and VIII (quinoline ester) demonstrated significant activity IC50 values 92.5 and 91.8µM respectively. Further molecular docking experiments were carried out for the synthesized compounds with 2y9w protein exhibited greater number of physical interactions for compounds VII and VIII than the other compounds in the series confirming the mushroom tyrosinase activity.